2005
DOI: 10.1534/genetics.105.044909
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Role of the med-1 and med-2 Genes in Specifying the Caenorhabditis elegans Endoderm

Abstract: The med-1 and med-2 genes encode a pair of essentially identical GATA factor-related transcription factors that have been proposed to be necessary for specification of the C. elegans endoderm (intestine or E lineage) as well as part of the C. elegans mesoderm. med-1 and med-2 are proposed to be the direct downstream targets and the principal effectors of the maternally provided SKN-1 transcription factor; med-1 and med-2 would thus occupy the pivotal interface between maternal and zygotic control of gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…We have previously reported that 50% of med-1,2(RNAi) embryos lack endoderm (Maduro et al, 2001). However, a recent study has shown that zygotic loss of med-1 and med-2 results in a weak or undetectable endoderm defect (Goszczynski and McGhee, 2005). We have since found that a significant maternal contribution of the MED genes exists, explaining this discrepancy (M.F.M., G.B.-M., I.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously reported that 50% of med-1,2(RNAi) embryos lack endoderm (Maduro et al, 2001). However, a recent study has shown that zygotic loss of med-1 and med-2 results in a weak or undetectable endoderm defect (Goszczynski and McGhee, 2005). We have since found that a significant maternal contribution of the MED genes exists, explaining this discrepancy (M.F.M., G.B.-M., I.…”
Section: Introductionmentioning
confidence: 91%
“…In the E cell, the MEDs contribute to the activation of the Especifying genes end-1,3, but are dispensable for E specification much of the time Goszczynski and McGhee, 2005;Maduro et al, 2001). We have previously reported that 50% of med-1,2(RNAi) embryos lack endoderm (Maduro et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In EMS (the mother of MS and E), SKN-1 activates the zygotic med-1 med-2 (med-1,2) divergent GATA factor gene pair (Coroian et al, 2005;Maduro et al, 2001). Loss of med-1,2 has a similar effect on MS specification as loss of skn-1, but a much weaker effect on E specification owing to parallel contributions to endoderm from SKN-1 and other factors (Goszczynski and McGhee, 2005;Maduro et al, 2005a;Maduro et al, 2001). In MS, MED-1,2 activate the T-box factor gene tbx-35 (Broitman-Maduro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the first protocol, embryos were collected 7-9 hr following injection of concentrated doublestranded RNA (dsRNA) into the maternal gonad; the rationale for such an early and limited observation period was to more effectively target the transient expression of the med-1/2 genes in the early embryo (Maduro et al 2001;Coroian et al 2006). In the more standard protocol, the RNAi effect is found to be maximally effective from 1 to 3 days following injection (Fire et al 1998;Zipperlen et al 2001;Goszczynski and McGhee 2005;Ahringer 2006); however, these more usual methods of administering RNAi show no effect with the med-1/2 genes (Kamath et al 2003;Goszczynski and McGhee 2005;Sonnichsen et al 2005). A second method of administering med-1/2 RNAi (Maduro et al 2001) was by means of a transgenic heat-inducible promoter driving expression of double-stranded med RNA (Tavernarakis et al 2000).…”
mentioning
confidence: 99%
“…Thus, the interpretation of Maduro et al (2007) requires that the putative maternal med transcripts are somehow susceptible to cosuppression and susceptible to RNAi for only a narrow window of several hours following injection (Maduro et al 2001), but are not susceptible to conventional (and usually much more powerful) RNAi effects that routinely persist for days. a med-1 dsRNA was injected at a concentration of $1 mg/ml by the protocol described previously , which is highly effective against either maternal or zygotic transcripts; i.e., it produces 100% arrested embryos/larvae when skn-1/elt-2 dsRNA is injected (Fukushige et al 2005;Goszczynski and McGhee 2005). Because of their high sequence similarity (Maduro et al 2001), injection of med-1 dsRNA should also target med-2 transcripts.…”
mentioning
confidence: 99%